One steps out of line—A “modern” Micraster species (Echinoidea, Spatangoida) with some old-fashioned look, Micraster ernsti sp. nov. from the Campanian (Cretaceous) - Schlüter, Nils (Zootaxa, 2024)
A new species of the micrasterid genus Micraster, Micraster ernsti sp. nov., is described from the Lower Campanian from the Hannover area (Lower Saxony, Germany). This species shows a peristome which is not close to the anterior margin, an only moderately-projecting labrum with a smooth rim and well-developed phyllodes, in contrast to contemporary Micraster species. These morphologies may have been the result of an adaptation to feeding from within the inhabited sediment, rather than from the sediment-water interface. This feeding strategy unveils an ecological niche not occupied by the co-occurring Micraster species.